Phonological Transfer in Javanese - Indonesian Bilingual Speech: Optimality Theoretic Insights for Language Education - Israul Husna; Dedy Suhery; Muhammed Jubran Naji Al-Mamri (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
This study investigates phonological interference in a bilingual context, focusing on how Javanese phonology influences the pronunciation of Indonesian. Using Optimality Theory (OT) as its primary framework, the study examines patterns of interference, their underlying causes, and their broader social and educational implications. Fieldwork was conducted in Gampong Karang Anyar, Langsa, Aceh, involving six students from SDN 1 Karang Anyar who are Javanese–Indonesian bilingual speakers. Participants were selected through purposive sampling based on their linguistic backgrounds. Data were collected through interviews and audio recordings and were qualitatively analyzed within the framework of Optimality Theory (OT). The findings reveal systematic phoneme shifts: /d/ changes to /t/ (ahad → [a.hat]), /f/ changes to /p/ (foto → [po.to]), and /b/ changes to /p/ (sabtu → [sa.ptu]). These shifts reflect the dominance of Javanese phonological constraints. The study adopts a qualitative approach supported by relevant linguistic literature. The results indicate that phonological interference strongly influences communication and language acquisition, resulting in a combination of features from both languages. These findings have direct implications for language education, highlighting the need for pronunciation instruction that anticipates bilingual transfer, curriculum design that incorporates contrastive phonological analysis, and teacher training that enables educators to distinguish random errors from systematic interference. By linking OT with classroom practice, this study contributes to a deeper understanding of phonological transfer in bilingual speech and its relevance to language education in multilingual Indonesian contexts. Ultimately, the study provides empirical evidence for the operation of OT constraints in Javanese–Indonesian bilingual speech, shedding light on patterns of phonological transfer and offering insights for pronunciation pedagogy in multilingual educational settings.